STRATEGI PENINGKATAN KUALITAS PEMBELAJARAN MATEMATIKA YANG BERORIENTASI PADA IMTAQ DI MAN TAMBAKBERAS JOMBANG - M. Tholib (EDUSCOPE: Jurnal Pendidikan, Pembelajaran, dan Teknologi, 2015)
Dualism curriculum system in use today both KTSP and Curriculum 2013 is still possible imbalances between aspects of professional scientific and moral aspects, so that there are various forms of irregularities committed by most people. Moral aspects include aspects of faith and piety could create the disciplined, honest, responsible for studying and developing. Teachers as the main actors of educational services in schools / madrasah has a very important role in efforts to increase faith and piety for students. In performing its duties, the teacher can associate the subject matter in taught it with religious values, which in turn leads to the increase of faith and piety. MAN Tambakberas Jombang is Islamic-based schools and boarding school founded in the Islamic Boarding School“Bahrul Ulum”Tambakberas Jombang, where 90% of students are students who live in huts with various types of religious activity that is very solid under the care by a Kyai. It would be very unfortunate if the learning of science and technology (in this case Mathematics), a madrasah teacher learning material did not manage to associate Islam with knowledge of the students. This is the factor causing the learning process becomes very boring, because students felt there was no connection between the mathematical study of the Islamic religion in the cottage. Though there are some teaching materials are in the process of learning mathematics teacher can integrate the aspect of increasing faith and piety to Allah SWT through activities structured learning. KEYWORDS: faith, piety, quality improvement, learning, mathematics, madrasah